2020
DOI: 10.2147/iprp.s179628
|View full text |Cite
|
Sign up to set email alerts
|

<p>Medication Therapy Management: Current Challenges</p>

Abstract: Medication therapy management (MTM) services have evolved as a means for pharmacists and other providers to assist patients and caregivers in improving therapeutic outcomes and reducing health care expenditures. More than a decade has passed since the Medicare Modernization Act of 2003 provided pharmacists with the opportunity to deliver MTM services to Medicare beneficiaries. MTM continues to offer pharmacists the opportunity to use their knowledge; yet, pharmacists have reported challenges with service deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 80 publications
1
45
0
Order By: Relevance
“…23 24 ADEs resulting from inappropriate drug prescribing, discrepancies between prescribed and current regimens, poor adherence, and the inadequate surveillance of adverse effects frequently lead to hospital admissions, readmissions 8 and other undesirable consequences such as increased morbidity, decreased autonomy, institutionalisation and even early death. 25 26 A systematic review by El Morabet et al 27 indicated ADE rates of 18%-38% after hospital discharge and 4.5%-24% hospital readmission rates due to those ADEs. Because older adults use more drugs, they are at a greater risk of drug-related readmission.…”
Section: Open Accessmentioning
confidence: 99%
“…23 24 ADEs resulting from inappropriate drug prescribing, discrepancies between prescribed and current regimens, poor adherence, and the inadequate surveillance of adverse effects frequently lead to hospital admissions, readmissions 8 and other undesirable consequences such as increased morbidity, decreased autonomy, institutionalisation and even early death. 25 26 A systematic review by El Morabet et al 27 indicated ADE rates of 18%-38% after hospital discharge and 4.5%-24% hospital readmission rates due to those ADEs. Because older adults use more drugs, they are at a greater risk of drug-related readmission.…”
Section: Open Accessmentioning
confidence: 99%
“…The first recommendation regarding the emphasis of expected benefits to patients has practice and policy-related implications. For example, in the US, medication therapy management (MTM) under Medicare Prescription Drug policy is a service often provided by community pharmacists [ 27 ]; however, the literature indicates lack of MTM uptake by some beneficiaries may be due to gaps in patient-friendly communication and marketing on MTM and its benefits [ 28 ]. Our toolkit items and specific strategies for this recommendation, including patient-facing print materials and scripted language for pharmacy team members, align with suggestions cited in the pharmacy practice literature [ 28 ] and could serve as a model for promoting adoption of other pharmacy services and related policies.…”
Section: Discussionmentioning
confidence: 99%
“… 91 Pharmacist's integration as a member of the healthcare team has been difficult to achieve because other members of that team especially physicians are not familiar with and/or are resistant to the extended clinical role of pharmacists. 100 , 105 , 106 , 109 , 112 , 113 , 114 …”
Section: The Key Barriers That Could Impede Chronic Disease Managemen...mentioning
confidence: 99%